Penilaian Risiko Kesehatan Kerja Area Graindryer PT Syngenta Seed Indonesia (SSI) - Firmansyah, Ervin; Dwiyanti, Endang; Martiana, Tri (FORIKES, 2024)
Work in the grain dryer area uses facilities and infrastructure such as machinery and electrical installations which are always faced with risks and sources of danger that can cause work accidents, work-related diseases and environmental pollution. Work risk assessment is one way to identify potential dangers that exist in each type of work in the grain dryer area. The aim of this research was to identify potential hazards, carry out hazard risk assessments and carry out appropriate hazard control in the grain dryer area. This research was a quantitative descriptive study, involving workers. Primary data was obtained from observations and interviews, while secondary data was obtained from company documents. The data obtained was analyzed descriptively. The research results showed that there were 32 potential hazards in the grain dryer area. Danger findings in the grain dryer area were biology, physics, ergonomics, psychosocial, mechanics, noise, nuisance, electricity, working at heights, pressurized systems, fire or explosion, confined spaces and other dangers. For the initial risk assessment, 14 moderate risks and 18 low risks were found. After controlling by suppressing dangerous consequences and risk management, the final risk assessment found 8 medium risks and 24 low risks. It was concluded that the risk control carried out by the company was complete.Keywords: hazard identification; work risk assessment; grain dryer ABSTRAK Pekerjaan di area graindryer menggunakan sarana dan prasarana seperti perangkat mesin dan instalasi listrik yang selalu dihadapkan pada risiko dan sumber bahaya yang dapat menimbulkan kecelakaan kerja, penyakit akibat kerja dan pencemaran lingkungan. Work risk assesment merupakan salah satu cara mengidentifikasi potensi bahaya yang terdapat pada setiap jenis pekerjaan area graindryer. Tujuan penelitian ini adalah mengidentifikasi potensi bahaya, melakukan penilaian risiko bahaya dan melakukan pengendalian bahaya yang tepat area graindryer. Penelitian ini merupakan studi deskriptif kuantitatif, yang melibatkan pekerja. Data primer diperoleh dari observasi dan wawancara, sedangkan data sekunder dari dokumen perusahaan. Data yang didapatkan dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa terdapat 32 potensi bahaya area graindryer. Temuan bahaya di area graindryer adalah biologi, fisika, ergonomi, psikososial, mekanik, kebisingan, nuisance, elektrik, bekerja di atas ketinggian, sistem bertekanan, api ata ledakan, ruang terbatas dan bahaya lain. Untuk penilaian risiko awal ditemukan 14 risiko sedang dan 18 risiko rendah. Setelah dilakukan pengendalian dengan menekan konsekuensi bahaya dan manajemen risiko, penilaian risiko akhir ditemukan 8 risiko risiko sedang dan 24 risiko rendah. Disimpulkan bahwa pengendalian risiko yang sudah dilakukan perusahaan sudah lengkap.Kata kunci: hazard identification; work risk assessment; graindryer